Proses Praktik Moderasi Beragama Masyarakat Konghucu di Desa Catur Kecamatan Kintamani Kabupaten Bangli - Ni Made Riani; I Nyoman Yoga Segara; I Nyoman Alit Putrawan (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2023)
The practice of religious moderation had actually been carried out well by several community groups in Bali before the Indonesian government echoed the religious moderation movement in public spaces. One of them that is so interesting and unique is the practice of religious moderation carried out by the Confucian community in Catur village. Its uniqueness is adhering to two cultural systems in their daily religious social life, namely: Chinese culture and Balinese culture. Every Hindu and Confucian holiday is celebrated together, so that in addition to the Pelinggih as a place for the Hindu Gods, there is also a Sinci as a place to worship the Gods and Ancestors of the Confucian community. Rites and rituals are carried out by applying the two systems between Confucianism and Hinduism, such as wedding and death processions which are carried out according to Balinese traditions and culture, and there are still many things that are carried out by Confucian people according to the culture of Hindu of Hindu people in Bali in their daily lives.